Qualidade do sono e alterações metabólicas em professores da rede pública de ensino - SILVA, Anne Caroline Silva e (2019)
Introduction: The teaching profession is considered by the International Labor Organization as one of the most stressful, because its attributions are not restricted to the classroom. Teachers are professionals of extreme importance to society and are subject to several stressors especially sleep deprivation. Sleep deprivation is associated with several adverse consequences, culminating in risk factors for cardiovascular disease. Objective: To verify the quality of sleep and possible metabolic changes in public high school teachers during a school semester. Methods: Longitudinal study with collection performed at the beginning and end of the school semester, in a Public State School, in the city of São Luís/MA. The data collected were life habits and health history, sleep quality; systolic and diastolic blood pressure; heart rate; anthropometric indices and blood sample (fasting) for determination of glucose, triglycerides and total cholesterol. Results: The sample consisted of 27 teachers with a mean age of 44.7 years. There was a higher prevalence of the female gender with 70.4% (19/27), as well as people with self-reported hypertension - 66.7% (18/27). Serum glucose concentrations (92.30 ± 19.177 vs 108.85 ± 45.640) and total cholesterol (161.00 ± 32.821 vs 173.59 ± 97.708) in the 1st and 2nd stages were statistically (p < 0.025 and p <0.001, respectively). However, the comparison between the serum concentration in the 1st and 2nd stage of triglycerides (211.74 ± 101.956 vs 194.56 ± 115.435) and mean values of systolic blood pressure (122.11 ± 18.71 vs 132.04 ± 27.85), diastolic (73.96 ± 11.30 vs 80.78 ± 16.09) and heart rate (74.00 ± 10.817 vs 71.67 ± 8.481) did not have a significant difference (p <0.604, 0.291 , 0.500 and 0.542, respectively). The subjective sleep quality variable, which deals with the perception about sleep quality of the individual, did not show statistically significant values (p <0.500) comparing the 1st and 2nd stages. In turn, poor sleep quality showed higher values in the second stage (66.7% vs 100%), as well as daytime sleep dysfunction (29.6% vs 33.3%), evidencing values statistically significant (p <0.001 for both parameters). Conclusion: Sleep quality variables presented significant differences between the stages of the study, mainly regarding quality, daytime dysfunction and sleep efficiency. As well as the results of the laboratory tests of blood levels of total cholesterol and glycemia, which suffered elevations in their parameters. These data show that the alteration in sleep quality affected the glycidic and lipid metabolism, and may be a triggering factor for cardiovascular diseases. However, due to the small sample size and short-term follow-up more studies in this area should be carried out.